2012
DOI: 10.1113/jphysiol.2012.238022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of the pyruvate dehydrogenase complex reduces statin‐mediated upregulation of FOXO gene targets and protects against statin myopathy in rodents

Abstract: Key points• Statin myopathy impairs phosphatidylinositol 3-kinase/Akt signalling and activates forkhead box protein O (FOXO) transcription factors in vivo in rodent skeletal muscle. This is associated with upregulation of downstream gene targets known to increase proteasomal and lysosomal-mediated protein breakdown, oxidative stress and inflammation, and inhibit muscle carbohydrate (CHO) oxidation.• We hypothesised that forcibly increasing muscle CHO oxidation in vivo, using the pyruvate dehydrogenase complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 80 publications
1
33
1
Order By: Relevance
“…In keeping with the post‐absorptive leg protein breakdown responses and lack of difference in muscle mass between statin myalgia and control volunteers, the post‐prandial increase in muscle protein synthesis was not blunted in statin myalgia, and contrasts what might have been expected based on the disruption of PI3k/Akt signalling in rodent statin myopathy (Mallinson et al . , ). Indeed, statin myalgic subjects in the present study showed no inactivation of the anabolic signalling proteins, p70S6k (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with the post‐absorptive leg protein breakdown responses and lack of difference in muscle mass between statin myalgia and control volunteers, the post‐prandial increase in muscle protein synthesis was not blunted in statin myalgia, and contrasts what might have been expected based on the disruption of PI3k/Akt signalling in rodent statin myopathy (Mallinson et al . , ). Indeed, statin myalgic subjects in the present study showed no inactivation of the anabolic signalling proteins, p70S6k (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred, at least in part, via inhibition of FOXO‐mediated transcription of genes regulating muscle CHO utilisation and protein breakdown (Mallinson et al . ). Additionally, meta‐data analyses associated intensive statin therapy (up to 40 mg day −1 ) with increased risk of new‐onset diabetes compared to moderate dose therapy (Preiss et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, impairment of pyruvate oxidation may lead to a chronic metabolic acidosis that may exacerbate bone demineralization, growth retardation, abnormal glucose tolerance, renal impairment and muscle wasting and contribute to a general pro-oxidant state associated with depletion of anti-oxidant defense mechanisms (3, 4). Given the broad spectrum of pathology associated with acute or chronic lactic acidosis, it is noteworthy that DCA stimulates residual PDC activity and decreases the adverse local tissue and/or systemic effects of lactic acidosis on cardiac or skeletal muscle function associated with exercise, insulin resistance, sepsis, ischemia, high fat feeding, or statin-induced myopathy and may inhibit tissue protein wasting (reviewed in 2, 19, 26). Together, these observations lend particular import to both circulating lactate as a clinically useful and readily obtainable biomarker of disease progression and to the potential utility of DCA in treating PDC deficiency.…”
Section: 1 Discussionmentioning
confidence: 99%
“…We were therefore interested to investigate whether administration of DCA could correct the impairment of CHO oxidation induced by simvastatin in a rodent model [57]. Compared with control, simvastatin (80 mg/kg/body weight) increased PDK4 protein expression and reduced muscle PDCa.…”
Section: Effect Of Dichloroacetate On Pdc Activity and Cho Oxidationmentioning
confidence: 99%